(untitled) (Journal of Hama University, 2024)
The study aims to compare the milking curve of dairy cows with chronic mastitis with healthy cows using Wood’s mathematical relationship during a full lactation season (305 days). The cows’ health and productivity records were studied during the period from October 2020 to October 2021. 120 cows (60 infected with mastitis and 60 healthy cows) were selected in the clinical trial, and data were collected on them through records of daily production and health status in the farms of the General Organization for Al-Mbagher. The results of this study recorded that the average production of healthy cows studied during the lactational season was (6529 kg/season), and the average production of cows infected with chronic mastitis during the lactational season was (4907 kg/season), as the average value of losses in milk production was (1623 kg/ Season) and the peak of production appeared in the week (4-8), then production decreased gradually until the cow dried up